Endiguement du Brahmapoutre et risques hydrologiques dans les territoires de la tribu Mising (subdivision de Dhakuakhana, Assam, Nord-est de l’Inde) - Émilie Cremin (VertigO)
In the northeast India, every year during the monsoon season, the Brahmaputra’s water level rises and the flood covers the plain of silt and sandy sediments. The Brahmaputra shows drastic changes in channel configuration which involves the erosion of cultivated land as well as villages. To control those dynamics, the territorial authorities have constructed embankments along the river bank in order to improve the land use and to protect human settlements. Nevertheless, the Mising tribe are living for long time with the floods. They practice divers types of paddy cultivation and varieties which can adjust with the heterogeneous agro-ecosystems. They also use to shift their settlements with the river channel’s divagations. When, protected by the embankment, the villagers are not prepared to receive floods if embankment breach suddenly. The communities can hardly shift the village on available lands when erosion give place to a river channel as the administrative regulations limits their mobility. The land rules and regulations do not allow to shift revenue village from place to place. The families become landless and need to find other ways to earn their livelihood. Therefore, in this paper, we are questioning if the embankment are protecting the people or if they are producing hazards to which the villagers have to adapt ?